Mismatch negativity (MMN) stands at the crossroads between explicit and implicit emotional processing. Issue 1 (18th August 2016) - Chen, Chenyi; Hu, Chia‐Hsuan; Cheng, Yawei
Abstract: The amygdala is known as a key brain region involved in the explicit and implicit processing of emotional faces, and plays a crucial role in salience detection. Not until recently was the mismatch negativity (MMN), a component of the event‐related potentials to an odd stimulus in a sequence of stimuli, utilized as an index of preattentive salience detection of emotional voice processing. However, their relationship remains to be delineated. This study combined the fMRI scanning and event‐related potential recording by examining amygdala reactivity in response to explicit and implicit (backward masked) perception of fearful and angry faces, along with recording MMN in response to the fearfully and angrily spoken syllables dada in healthy subjects who varied in trait anxiety (STAI‐T). Results indicated that the amplitudes of fearful MMN were positively correlated with left amygdala reactivity to explicit perception of fear, but negatively correlated with right amygdala reactivity to implicit perception of fear. The fearful MMN predicted STAI‐T along with left amygdala reactivity to explicit fear, whereas the association between fearful MMN and STAI‐T was mediated by right amygdala reactivity to implicit fear. These findings suggest that amygdala reactivity in response to explicit and implicit threatening faces exhibits opposite associations with emotional MMN. In terms of emotional processing, MMN not only reflects preattentive saliency detection but also stands at the crossroads of explicit and implicit perception. Hum Brain Mapp 38:140–150, 2017 . © 2016 Wiley Periodicals, Inc.